Topical Treatment of Persistent Epithelial Defects with a Matrix Regenerating Agent - TOKER, AYŞE EBRU; SEVİK, MEHMET ORKUN; AKKAYA TURHAN, SEMRA (MARY ANN LIEBERT, INC, 2018)
Purpose: The aim of the study was to assess the efficacy of a topical regenerating agent (RGTA) for management of persistent epithelial defects (PEDs) resistant to conventional therapy. Methods: Twenty-one patients (23 eyes) with PEDs despite the use of conventional therapy for lagophthalmos (n = 4), neurotrophic ulcer (n = 9), chemical burn (n = 3), Stevens-Johnson syndrome (n = 1), atopic keratoconjunctivitis (n = 1), severe dry eye (n = 2), peripheral ulcerative keratitis (n = 1), fungal keratitis (n = 1), and bacterial keratitis (n = 1) were enrolled in the study. Patients were treated with RGTA (Cacicol; Thea, Paris, France) instilled at a dosage of one drop on alternate days. Patients were evaluated by slit-lamp examination, anterior segment photography, and fluorescein-dye testing. Ulcer areas were noted on alternate days starting from the first day of instillation. Results: Twenty of 23 eyes (86.9%) displayed complete corneal healing after a mean period of similar to 7.2 days (range, 2-20 days). Mean decrease ratio of ulcer area observed was 61.2% (range, 8.8%-100%, n = 19) on the 2nd day, 74.4% (range, 36%-100%, n = 16) on the 4th day, 80.2% (range, 43.7%-100%, n = 12) on the 6th day, 88.5% (range, 55.9%-100%, n = 9) on the 8th day, and 85.5% (range, 58.3%-100%, n = 7) on the 10th day. No significant differences were found in the epithelialization speed between eyes with and without bandage contact lenses in any postoperative day (P > 0.05). There were no treatment-related local or systemic side effects during the study. Conclusions: RGTA seems to be an effective therapeutic alternative in the treatment of persistent corneal epithelial defects.
Keywords: regenerating agent; RGTA; persistent epithelial defect; recalcitrant epithelial defect; Cacicol; CORNEAL CROSS-LINKING; THERAPY AGENT; RGTA; SULFATE